Kristaluria disertai Azotemia dan Uremia pada Kucing - Hary Purnamaningsih; Soedarmanto indarjulianto; Maria Yunitasari; Maulidina Ahmadi; Luh Putu Nadya Santika; Sitarina Widyarini; Sugiyono sugiyono (Jurnal Sain Veteriner)
ABSTRAK